Fractured phalanx in a violinist‘s finger: Special considerations in treating musician patients - Gibson, Julia; Williams, Jason (DALHOUSIE MEDICAL JOURNAL, 2009)
Post-traumatic reconstructive surgery on musician patients is uniquelchallenging in that sustained motor deficits imperceptible to the average person can be debilitating for this population.1 Instrument manipulation is extremely physically demanding; even without trauma musicians are at risk of developing a musculoskeletal disorder from mere overuse of the muscles involved in their craft.2 Furthermore, the link between physical and emotional well-being is exaggerated in musicians, as their livelihood revolves around the physical expression of emotion.3 Analyzing medical treatment from a musician‘s perspective provides a useful demonstration of the increased efficacy in utilizing a whole person approach as opposed to one that is strictly biomedical.4 Heightened sensitivity to motor deficits and the economic and emotional implications thereof are significant factors pertaining to the lifestyle of these patients, and treatment should be tailored accordingly.